Contracts Selection Under Quality Uncertainty in Refurbish Decisions - Yang Bai; Wenqi Song; Xingshuai Wang (IEEE Access, 2022)
With the rapid development of the information technology industry, refurbished products play significant roles in this challenge of environmental, economic, and social performance revolution. Meanwhile, when the refurbished product is launched in the market compete with new products, how and whom to repair the used products effectively and what kind of effective coordinate incentive mechanisms utilized to alleviate conflict and achieve the challenge become one of the most significant issues. Therefore, this study compares two refurbishing structures (manufacturer refurbishing and retailer refurbishing) under three different contract incentive mechanisms (wholesale price, revenue sharing, and reward points contracts) in two periods closed-loop supply chain (CLSC) model with demand uncertainty. Our results show that the manufacturer should allow his retailer to refurbish used products under the condition of using reward points contract strategies. It will help improve the whole channel performance and create much higher profits. Meanwhile, all channel members benefit from the reward point contract in the manufacturer refurbishing scenarios. However, manufacturers prefer revenue-sharing contracts while retailers prefer wholesale price contracts in the retailer refurbishing scenarios.